The effects of a high Glycemic Index diet on pancreatic cancer - Eleni Valtzis (2019)
Sugar and its abundance in the modern diet have long been suspected for the indirect infliction and deterioration of several diseases. From the beginning of the industrialization until today, sugar consumption has nearly increased tenfold, with the biggest growth shown in the past 50 years. In the 1920s, a scientist named Otto Heinrich Warburg discovered that cancer cells demonstrate metabolic changes with a preference in glucose. Since then, scientists have tried to decode this metabolic phenotype and track the role of sugar in cancer. Considering the hypothesis of Warburg, that sugar seems to be feeding cancer cells in different types of cancer, the present dissertation is trying to detect whether it could also be regarded as a risk factor for the ignition of the disease on the example of pancreatic cancer. Pancreatic cancer is one of the most lethal types of cancer with a very poor future prognosis. To examine the connection, a hypothesis is built which connects pancreatic cancer with a diet of high glycemic index. The results of the present research show no connection between a high glycemic index diet and ignition of the disease. However, there seems to be grave need of accessible annual screening methods for pancreatic cancer. This absence appears to interfere with the execution of well designed cohort studies. As a result, the present dissertation suggests further research implemented on large cohorts in earlier stages of life.